ECONOMIES OF THE INTERNET I: INTERSECTIONS - Jarrett, Kylie; Velkova, Julia; Jakobsson, Peter; Graham, Roderick; Gehring, David (AoIR Selected Papers of Internet Research, 2015)
The internet has increasingly been conceptualized as a space of economic activity. This contemporary imaginary has been particularly influenced by insights from the school of Autonomist Marxism in the foundational work of Tiziana Terranova and through the dominance of Christian Fuchs’ application of Marxist economic concepts. While this has generated great insight into the political economy of the internet, and in particular allowed for the conceptualization of user activity as labor, this approach is only one paradigm for considering the economic activities and implications of the internet. For internet research, there is also the need to move beyond the long schism between political economy and cultural studies as we try to understand user activity that is socially and affectively rich, but emerges from commercial contexts. This series of panels proposes to expand the exploration of the internet as an economic construct in a number of directions. It pluralizes the definition of “economy”, expanding it from the strictly fiscal to include other economies such as the moral, (sub-) cultural, affective, queer, or libidinal (to name merely a few). Various papers propose different economic models for understanding the interactions within and between these various economies. They also expand the range of actors and economic contexts associated with the internet, drawing attention to the intersections of race and gender in particular. The goal of these papers across the various sessions is to expand our imaginary of the internet economy. This panel is focused on expanding critical frameworks that can be brought to bear on economies within digital media. While Marxian frameworks are insightful and valuable, they may not adequately reflect the contemporary social context, nor engage effectively with politics outside of class. What other economic models need to be used, or how do we inflect Marx, for these contexts? What other critical perspectives do we need to incorporate to understand the broad implications of a socially pervasive, but commercial internet? The papers on this panel work at the intersection of economic concepts and theoretical paradigms drawn from a variety of disciplines, demonstrating an expanded toolkit for interrogating internet economies. The first speaker offers a Marxist feminist and queer critique of theories about user exploitation that follow from the Autonomous Marxists, calling upon us to recognize the gendered and racialized history of unpaid labor and the absence of this insight in neoclassical economic modeling. Through a case study in the political economy of anonymity in queer dating/hook-up sites, the speaker de-centers the normatively white, hetereosexual, cis-male in economic models, highlighting different and too-frequently ignored ways of understanding privacy and the exploitation of data. The second speakers return to and revitalize classic work on gift economies, exploring the ways in which the fiscal and moral economies are articulated together in commons-based production. Through a multi-sited ethnographic study of open source animation film-making communities tracing the movement between actors and objects across different regimes of value, the speakers describe negotiated transitions from commons to commodity and back again. They argue that when engaging with producers’ own accounts of their community-based processes and the agonistic ethics holding sway there, we are better able to see the fluid dynamics of decommodification and recommodification taking place within commons production integrated into the commodity-based capitalist economic environment. The third speaker looks at the intersection of state policy and economics, providing a history of how the internet, which was focused on non-profit and public concerns in the first half of its life (1965–1995), was refigured by U.S. law and policy to support corporate for-profit use. Starting with the Telecommunications Act of 1996, through the Digital Millennium Copyright act of 1998, the FCC Policy Statement of 2010, and the National Broadband Plan of 2010, the speaker argues that U.S. law and policy have attempted to increase competition where market-based solutions are not clearly in the public interest, placing increasingly more informational functions within the purview of market forces. The speaker then addresses policies at access and content levels that would instead nurture and grow non-profit spaces. The fourth speaker continues the broad political engagement of this panel, examining crowdfunding campaigns set up to support U.S. police officers involved in the 2014 killings of Michael Brown and Eric Garner. The speaker argues that these examples of gift economies, by simply claiming to e.g. “help [Officer Darren Wilson] and his family during this trying time in their lives,” collapse the roles Fuchs has described as socio-cultural, social-political, and socio-economic, and allow racist donors to “launder” their politico-economic activity through the gift economy. This case study demonstrates the importance of integrating economic analysis with critical social theory—the central project at the heart of this panel.